Interdisciplinary perspectives on the development, integration, and application of cognitive ontologies - Hastings, Janna; Frishkoff, Gwen A.; Smith, Barry; Jensen, Mark; Poldrack, Russell A.; Lomax, Jane; Bandrowski, Anita; Imam, Fahim; Turner, Jessica A.; Martone, Maryann E. (Frontiers in Neuroinformatics, 2014)
We discuss recent progress in the development of cognitive ontologies and summarize three challenges in the coordinated development and application of these resources. Challenge 1 is to adopt a standardized definition for cognitive processes. We describe three possibilities and recommend one that is consistent with the standard view in cognitive and biomedical sciences. Challenge 2 is harmonization. Gaps and conflicts in representation must be resolved so that these resources can be combined for mark-up and interpretation of multi-modal data. Finally, Challenge 3 is to test the utility of these resources for large-scale annotation of data, search and query, and knowledge discovery and integration. As term definitions are tested and revised, harmonization should enable coordinated updates across ontologies. However, the true test of these definitions will be in their community-wide adoption which will test whether they support valid inferences about psychological and neuroscientific data.